Whole-body vibration exposure of roller compactor operators: characteristics and effect of waste rubber in damping the vibration. Issue 3 (3rd July 2021) - Madhavie, Migunthanna Kariyakaranage Janitha; Subashi De Silva, Gardiyas Hewawasam Mummullage Jimila
Abstract : Whole-body vibration (WBV) exposure of 12 roller compactor operators were measured to investigate the characteristics of WBV transmitted to the roller compactor operators and to assess their level of exposure to WBV. All of the subjects were in the seated position and vibration transmission at the interface between the operator and seat was measured. Operators showed a dominant WBV transmission in the vertical direction. Eight-hour exposure and the vibration dose value were used to assess operators' exposure to WBV. In total, 75% of operators had high or moderate potential health risk defined in the health guidance caution zone speciﬁed in Standard No. ISO 2631-1:1997. A rubber mat produced with waste rubber sludge was used to investigate the effect of damping the vibration transmitted to the operator. The rubber mat damped the WBV transmission in all three directions: 18% in vertical, 5% in lateral and 2% in fore-and-aft directions.